2021
DOI: 10.1017/wtc.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

Comparing optimized exoskeleton assistance of the hip, knee, and ankle in single and multi-joint configurations

Abstract: Exoskeletons that assist the hip, knee, and ankle joints have begun to improve human mobility, particularly by reducing the metabolic cost of walking. However, direct comparisons of optimal assistance of these joints, or their combinations, have not yet been possible. Assisting multiple joints may be more beneficial than the sum of individual effects, because muscles often span multiple joints, or less effective, because single-joint assistance can indirectly aid other joints. In this study, we used a hip–knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 55 publications
(102 reference statements)
5
62
0
Order By: Relevance
“…Franks et al . used HIL optimization on a hip-only exoskeleton and found that across three participants the average optimal assistance magnitude on the hip extension was 0.404 Nm kg −1 47 , ~ 47% of peak biological hip extension torque (Supplementary Table S6 ; condition). Furthermore, Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Franks et al . used HIL optimization on a hip-only exoskeleton and found that across three participants the average optimal assistance magnitude on the hip extension was 0.404 Nm kg −1 47 , ~ 47% of peak biological hip extension torque (Supplementary Table S6 ; condition). Furthermore, Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…One recently developed technique to identify an individualized, optimal profile of assistance is human-in-the-loop (HIL) optimization, where the value of a physiological objective (e.g., metabolic cost) is estimated in real-time (with a human in the loop) and used to identify optimal device parameters for each participant 8 , 11 , 22 , 44 , 47 52 . The motivation of this approach is to tackle high inter-participant variability in response to any given assistance, implying that assistive profiles that help one participant may hinder another.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it is possible that assisting incline walking may be less effective because of the related effect of walking speed: people tend to walk slower up inclines [33], [34], [35], [36], and exoskeletons have been less effective at slower speeds [7], [37]. To see if larger improvements to incline walking are possible, the best strategy may be to optimize whole-leg assistance using a device with large torque capabilities [7], [38].…”
Section: Introductionmentioning
confidence: 99%
“…However, the hips, knees, and ankles all contribute to the total positive power of the leg during incline walking [30], [31], so assisting all joints simultaneously could be best. While knee assistance has been the least effective of all joints on level ground [38], biological knee torque and power increase as grade increases [31], meaning the knee may be increasingly helpful to assist with inclines. For level-ground walking, whole-leg assistance produced greater improvements to metabolic cost compared to single-joint and two-joint assistance [38], consistent with expectations from biomechanical simulations [40], [41].…”
Section: Introductionmentioning
confidence: 99%